(untitled) (Third Sector Social Economic Review, 2024)
The concept of philanthropy, which has become established in the international third sector (civil society) literature, has recently been examined in an important dimension for businesses. It enhances firms to intervene in social and economic regulations from disparate perspectives. Due of the concept’s ambiguous definition, philanthropy is frequently referred to as charity. However, the term was separated from philanthropy after it was coined by the Third Sector Foundation of Turkey (TUSEV). Philanthropy is defined as actions in which donations are ongoing, as opposed to charity, which is a one-time act of assistance or donation by corporations. The principle of ""doing good by doing good"" is the foundation of philanthropy, which is defined as love of humanity. The moral, ethical, and emotional motivations of people and organizations are what define philanthropy. Philanthropy practices provide permanent solutions in the long term. At this point, in their philanthropy practices, businesses focus more on what they aim to change in society. Any long-term impact that corporations voluntarily have on society can be assessed in the context of philanthropic endeavors. This study primarily set out to investigate the importance of the philanthropy concept. The fact that the concept of philanthropy creates a confusion of meaning in Turkish has made it necessary to examine the concept in detail. This article’s goal is to investigate the idea of philanthropy and highlight how it differs from related ideas.